META-ANALYSIS: THE EFFECT OF THE PROJECT-BASED LEARNING MODEL ON STUDENTS' MATHEMATICAL CREATIVE THINKING ABILITIES IN INDONESIA 2021-2025 - Fitriyani Perouka; Baharuddin; Muhammad Fachri B. Paloloang (RADJA PUBLIKA, 2026)
This study aims to comprehensively analyze the effect of the Project Based Learning model on students' mathematical creative thinking abilities in Indonesia in 2021-2025. This study used a meta-analysis method with PRISMA guidelines and obtained 13 primary studies for analysis. Primary studies that met the inclusion criteria were analyzed using Comprehensive Meta-Analysis (CMA) software version 4.0. The results of the calculation of the overall effect size obtained a Hedges'g value of 1.063 with a Z value of 7.990 and a p value <0.05, which means that the application of the Project Based Learning model has a significant effect on students' mathematical creative thinking abilities. Based on the results of the moderator variable analysis, a very large effect size was obtained at the high school level with a Hedges'g value of 1.487 and in studies with a small sample size (≤30 participants) with a Hedges'g value of 1.121. However, the heterogeneity test between groups obtained a p value>0.05 for both moderator variables, so that the differences between groups were not statistically significant and did not provide sufficient evidence that education level or sample size moderated the intervention effect.